BENTUK PENGEMBANGAN PENDIDIKAN MULTIKULTURAL DI INDONESIA - Adelia Shintia Ningrum (Habitus: Jurnal Pendidikan, Sosiologi, & Antropologi, 2025)
ABSTRACTMulticultural education in Indonesia plays a critical role in addressing the nation's vast diversity in culture, religion, and language. This study explores the theoretical, policy, and practical developments of multicultural education in the Indonesian context. Using a qualitative approach and narrative literature review, the research analyzes key dimensions such as the integration of Pancasila values, the development of inclusive teaching methods, and the challenges of implementation. Findings reveal that while significant progress has been made, obstacles remain, including infrastructural disparities and limited educator capacity to implement multicultural principles effectively.The study highlights the potential of digital technology and global-local integration to enhance the effectiveness of multicultural education. Recommendations include developing contextually relevant policies, strengthening local implementation capacities, and fostering stakeholder collaboration. Future research is needed to design adaptive and transformative educational models. Multicultural education is presented not only as a necessity but also as a strategic imperative for building an inclusive and cohesive Indonesian society capable of meeting global challenges while maintaining its cultural authenticity.Keywords: Cultural Diversity; Education Policy; Globalization; Inclusive Pedagogy; Multiculturalism ABSTRACTPendidikan multikultural di Indonesia memiliki peran penting dalam menghadapi keberagaman budaya, agama, dan bahasa yang sangat luas. Penelitian ini mengeksplorasi perkembangan teoretis, kebijakan, dan praktik pendidikan multikultural dalam konteks Indonesia. Dengan pendekatan kualitatif dan kajian literatur naratif, penelitian ini menganalisis dimensi utama seperti integrasi nilai-nilai Pancasila, pengembangan metode pembelajaran inklusif, serta tantangan dalam implementasinya. Hasil penelitian menunjukkan bahwa meskipun terdapat kemajuan signifikan, hambatan seperti disparitas infrastruktur dan kapasitas pendidik yang terbatas dalam menerapkan prinsip multikultural masih menjadi tantangan.Penelitian ini menyoroti potensi teknologi digital dan integrasi lokal-global untuk meningkatkan efektivitas pendidikan multikultural. Rekomendasi mencakup pengembangan kebijakan yang relevan secara kontekstual, penguatan kapasitas implementasi di tingkat lokal, dan kolaborasi antar pemangku kepentingan. Penelitian lanjutan diperlukan untuk merancang model pendidikan yang adaptif dan transformatif. Pendidikan multikultural dipaparkan tidak hanya sebagai kebutuhan tetapi juga sebagai imperatif strategis untuk membangun masyarakat Indonesia yang inklusif dan kohesif serta mampu menghadapi tantangan global sambil mempertahankan keautentikan budayanya.Kata Kunci: Kebijakan Pendidikan; Keberagaman Budaya; Multikulturalisme; Pedagogi Inklusif; Teknologi Digital